Natural Experiment on the Extraction and Quenching of Rapakivi-like Magmas: Traces of Interaction with the Mafic Melts and Their Derivatives, Salmi Batholith (Karelia, Russia) - Artem Konyshev (Minerals, 2023)
The origin of the anorthosite-rapakivi granite-bearing rock complexes was a topic of research for geologists for more than a century. Magmatic systems that produce these complexes were widely developed in the Precambrian and have no direct analogues in modern times. The main goal of this study was to characterize the conditions under which primitive granitoids formed and to shed light on the history of ore matter transport during these stages. The object of the research was granite porphyry dikes—a subeffusive analogue of rapakivi granite from the Salmi batholith in the Fennoscandian Shield. Characteristic solid-phase inclusions of a mineral paragenesis of mafic rocks, as well as inclusions of sulfide melts, were found in zircon from this type of rock. These sulfide inclusions were homogenized by heating, and subsequently, the trace element composition was determined by the LA-ICP-MS method. The geochemistry of zircons was studied by the SIMS method, and the temperature of their formation was determined using a Ti-geothermometer. The temperature of the studied zircon grain formation varied from 925 to 765 °C. The values of ƒO2 for the early stages of the rock formation were in the region below the boundary of the FMQ buffer. The presence of two sulfide melts at the time at which the sulfide inclusions were captured by the zircon, pyrrhotite-chalcopyrite, and sphalerite-chalcopyrite compositions was established. The capture of sulfide inclusions from the pyrrhotite-chalcopyrite composition occurred above 841 °C, while in sphalerite-chalcopyrite, they occurred at a lower temperature of 765 °C. The connection between the formation of granite porphyry with mafic melts that form rocks of the gabbro and anorthosite types was established.